Biomarkers of infection in the optimization of antibacterial therapy: justified expectations - Kulabukhov V.V.; Shabanov А.К.; Andreeva I.V.; Stetsiouk О.U.; Andreev V.А. (Клиническая микробиология и антимикробная химиотерапия, 2020)
Despite the continuous improvement of approaches to antimicrobial therapy and the emergence of new highly effective antibiotics, severe bacterial infections being a significant cause of morbidity and mortality remain a top of mind issue for clinicians. Immediate initiation of the effective antibiotic therapy is an essential component of the successful treatment of serious bacterial infections, and therefore, special attention should be paid to the timely diagnosis. Measurements of biomarkers of inflammation (C-reactive protein, procalcitonin, presepsin, proadrenomedullin) in combination with clinical evaluation are important at first for the diagnosis of bacterial infection, and after that these can help to assess the clinical response to therapy and determine the time-point of antibiotics withdrawal. This review presents the characteristics of the main markers of inflammation, discusses the situations when determination of biomarkers is appropriate, and also provides modern clinical recommendations and algorithms regarding the use of these diagnostic markers in the management of patients with bacterial infections.